An Outline on Vasicine, its Ethnomedical and Nanoformulation Approach. Issue 1 (2nd January 2021) - Kumari, Nidhi; Akhtar, Juber; Ahmad, Mohammad; Badruddeen,; Khan, Mohammad Irfan
Abstract: Vasicine (VAS) is mainly obtained from Adhatoda vasica Nees or Justicia adhatoda (Malabar nut, Adosa), family Acanthaceae. In the present work, we have elaborated chemistry, pharmacology, molecular docking, future prospective, and analytical methods of determination of VAS in various existing formulations. VAS possess a wide range of biological activities like analgesic, anti-microbial, anti-inflammatory, anti-cancer, anti-hypertensive, anti-HIV, antioxidant, anticonvulsant, antimalarial, and anti-tubercular activities. There are many marketed formulations of VAS in the traditional systems of medicines. The potential expectations for developing nanosized drug delivery systems (dendrimers, liposome, polymeric nanoparticles, nano-emulsions, and micelles) may help to improve solubility, absorption, plasma half-life, bioavailability, and the overall efficacy of VAS.